2017
DOI: 10.1007/s10151-017-1731-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative use of ICG fluorescence imaging to reduce the risk of anastomotic leakage in colorectal surgery: a systematic review and meta-analysis

Abstract: ICG fluorescence imaging seems to reduce AL rates following colorectal surgery for cancer. However, the inherent bias of the non-randomized studies included, and their differences in AL definition and diagnosis could have influenced results. Large well-designed RCTs are needed to provide evidence for its routine use in colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
173
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(205 citation statements)
references
References 43 publications
3
173
0
6
Order By: Relevance
“…Although they found a 6.1% rate of skin necrosis in the non-ICGA group versus 2.2% in the ICGA group, this difference was not statistically significant [29]. In addition to the assessment of abdominal skin and ALT flap perfusion, ICGA serves as an effective tool to assess anastomotic bowel perfusion [30]. Moreover, it could have a role in reducing anastomotic leakage rates following ECF resection, which reflects the potential for implementation of ICGA in reconstructive abdominal wall surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although they found a 6.1% rate of skin necrosis in the non-ICGA group versus 2.2% in the ICGA group, this difference was not statistically significant [29]. In addition to the assessment of abdominal skin and ALT flap perfusion, ICGA serves as an effective tool to assess anastomotic bowel perfusion [30]. Moreover, it could have a role in reducing anastomotic leakage rates following ECF resection, which reflects the potential for implementation of ICGA in reconstructive abdominal wall surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, avoidance of ischaemia during the initial fashioning of the anastomosis is important. A recent multi‐institutional study (PILLAR II) and a systematic review and meta‐analysis suggest that intra‐operative use of indocyanine green fluorescence imaging may reduce the risk of AL in colorectal surgery by ensuring adequate perfusion of the anastomosis. Perfusion assessment before making the anastomosis may prevent anastomotic ischaemia as a postoperative complication.…”
Section: Discussionmentioning
confidence: 99%
“…Our utilization of IFI reduced the AL rate by half, in agreement with a recent meta-analysis, which found that the AL rate in rectal cancer operations was significantly lower with than without IFI (1.1% vs 6.1%). 22 Although the primary cause of AS is regarded as chronic ischemia around the anastomotic site, objective observations are still unavailable. Reduced IFI intensity was the independent parameter that correlated with AS.…”
Section: Discussionmentioning
confidence: 99%